Synthesis, structural and semiconducting properties of Ba(Cu1/3 Sb2/3)O3-PbTiO3 solid solutions - Singh C.B.; Kumar D.; Prashant; Verma N.K.; Singh A.K. (My University, 2025)
We report the synthesis and properties of a new solid solution 0.05Ba(Cu1/3Sb2/3)O3-0.95PbTiO3 (BCS-PT) which shows the semiconducting properties. In this study, we have designed new perovskite-type (ABO3) solid solution of BCS-PT that have tunable optical band gap. BCS-PT compounds were prepared by conventional solid-state reaction method and their structural, micro-structural and optical properties were analyzed. The calcination temperature for BCS-PT solid solutions has been optimized to obtain a phase pure system. The Reitveld analysis of X-ray data show that all samples crystallize in tetragonal crystal structure with space group P4mm. X-ray investigation revealed that increase in calcination temperature led to increase of lattice parameter 'a' while 'c' parameter value lowered. The band gap of PbTiO3 is reduced from 3.2 eV to 2.8 eV with BCS doping and with increasing calcination temperature it further reduces to 2.56 eV. The reduced band gap indicated that the compounds are semiconducting and can be used for photovoltaic device applications. © 2018 Author(s).